Report on an unannounced inspection of Ash House Women's Prison Hydebank Wood, 9 - 19 May 2016. (2016) - Northern Ireland., Criminal Justice Inspectorate,; Northern Ireland., Department of Education., Education; Training Inspectorate,; Great Britain., Her Majesty's Chief Inspector of Prisons for England; Wales,; Northern Ireland., Regulation; Quality Improvement Authority,
No abstract available